Bibliometric analysis of the literature on startups and strategic alliances - Silveira, Bruno Ribas (2019)
The present study aims to select a bibliographic portfolio of relevant articles on two main axes: startups and strategic alliances, with the purpose of performing bibliometric analyzes of the articles and their references, authors and periodicals relevant to the theme published in the period between 2013 and 2018. The selection of this portfolio aims at forming the core of a bibliographical reference referring to the subjects in question. As an intervention tool to select the articles, the tool named ProKnow-C was used. The process identified 16 relevant articles that were aligned with the study context. After the selection of the articles, a bibliometric analysis of this portfolio was carried out, evidencing the most relevant articles, the authors and the periodicals that published the most on the two axes studied. In the same way, the bibliometric analysis of the references of the selected final portfolio was also carried out. With the results, this research may be useful for academics and practitioners who wish to develop their theoretical frameworks on articles, authors and journals that stand out in this area and in the context in question.